Complete Solutions of Nonhomogeneous Plastic Plates Reskin on Nonrigid Beams - Rytwińska, D.; Kwięciński, M. (Engineering Transactions, 1983)
A semi-inverse method is developed to obtain exact solutions to thin, rigid-ideally plastic plates resting on beams that are capable of deflecting together with the edges of the plates. The structural members of the plate-beam systems are assumed to obey the Huber-Mises yield condition. The structure is subjected to a transverse, uniformly distributed load and is point supported at the corners. New complete solutions are arrived at for isotropic plates in the shape of a square, a rectangle, a rhombus and a paallelogram. Orthotropic plates are also dealt with in the orthogonal situations. The obtained results make it possible to prescribe such a type of nonhomogeneity that the whole structure becomes plastic at the same intensity of load.